(untitled) (Hematology Meeting Reports, 2009)
Severe combined immunodeficiency (SCID) is a rare congenital defect of immunity that, if promptly diagnosed, can be cured by stem cell transplantation. The Pediatric Department of the University of Brescia is the national referent center for diagnosis and treatment of children affected by SCID. Since 1990 more than 100 affected children were admitted within the unit.